Januari efek di Bursa Efek Indonesia, Bursa Efek Amerika, Bursa Efek Jerman, dan Bursa Efek Jepang sebelum, sesaat dan sesudah pandemi Covid-19 - Ulfarizty, Zahra Putri; Komariah, Siti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Many factors can affect the movement of stock prices in the capital market. Investors can use these factors as a reference in making investment decisions. One of them is the Market Anomaly. Based on the existing anomalies, the seasonal anomaly is the most frequently studied anomaly seen from its effect on company stock returns. One of the categories of seasonal anomaly is the January Effect. This study aims to find out how the January effect phenomenon is on the Indonesian, American, German, and Japanese Stock Exchanges for the period 2019 - 2021. In addition to knowing whether there are differences in stock returns between January and other months, and to find out whether there are differences in stock returns on the stock exchange effects of Indonesia, America, Germany, and Japan during the study period. The data used is the weekly primary stock price index data for the period January 2019 to December 2021. The research method used is the comparative method and event study. While the analysis technique used is the normality test, homogeneity test, Anova test, and post hoc test. The results showed that there was no January effect on the Indonesian, American, German and Japanese stock exchanges because there was no significant difference in the average stock return value between January and other months.